Factors Related to WCA (Women of Childbearing Age) in Early Detection of Cervical Cancer with IVA Method - Laurena Ginting (Science Midwifery, 2020)
Cervical cancer attacks the cervix in the lower third of the uterus. In Indonesia, The highest cancer that occurs in women is cervical cancer and 65% of the incidence is found in the advanced stage, 18.5% occurs at the age of 25-34 years and the highest incidence of cervical cancer occurs at the age of 45-54 years. This type of research is descriptive of analytics with a cross-sectional approach. The samples in this study were women of childbearing age-aged 20-65 years. the sampling technique is a purposive sample. Analysis of data in the form of univariate (Frequency and percentage) and bivariate with the chi-square test. The results of the study age with a value of p = 0.207 where the value of p > is 0.05 and with a value of p = 0.207 where the p-value > 0.05. Jobs with a value of p = 0.004 where the p-value > 0.05, Support Husband value p = 0.004 where the p-value > 0.05 and Knowledge value p = 0.004 where the p-value > 0.05 can then be inferred in the absence of age relations, education of women of childbearing age in conducting IVA test checks. Job, Husband, and Knowledge Support has a relationship with women of Childbearing Age in conducting iva test examinations. It is recommended to further enhance the role of the husband, the role of health workers is also very important to motivate the community in conducting early detection.